Market Segmentation and Targeting Analysis for Online Food Delivery in Jabodetabek, Indonesia - Aulia, Naila; Akhmad, Nafila Nuraini; Ramadhia, Kahti; Rahayu, Fatik (Golden Ratio of Mapping Idea and Literature Format, 2026)
This study examines market segmentation and targeting strategies for online food delivery applications in Jabodetabek. It employs primary data collected through online questionnaires from 150 active users of food delivery apps, aged 17 and above, who used the services at least three times in the past month. The research utilizes a descriptive approach with hierarchical and K-means cluster analysis to segment users based on demographic and psychographic characteristics, focusing on the 7P marketing mix attributes. The results reveal two distinct market segments, with the first segment, characterized by a high preference for convenience and accessibility, identified as the most promising target due to its higher mean score (3.98) for using apps when time-constrained or hungry. This segment values practical features like real-time order tracking and diverse menu options. The findings indicate that users prioritize ease of use, promotional offers, and professional courier services, with less sensitivity to price when service quality is satisfactory. The study highlights the importance of understanding consumer preferences for tailored marketing strategies in the competitive food delivery industry.